2022
DOI: 10.1182/bloodadvances.2021006034
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B-cell lymphomas in adults with aberrant coexpression of CD10, BCL6, and MUM1 are enriched in IRF4 rearrangements

Abstract: Diffuse large B-cell lymphoma (DLBCL) with aberrant coexpression of CD10+BCL6+MUM1+ (DLBCL-AE), classified as germinal center B cell (GCB) type by the Hans algorithm (HA), was genetically characterized. To capture the complexity of DLBCL-AE, we used an integrated approach that included gene expression profiling (GEP), fluorescence in situ hybridization, targeted gene sequencing, and copy number (CN) arrays. According to GEP, 32/54 (59%) cases were classified as GCB-DLBCL, 16/54 (30%) as activated B-cell (ABC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 32 publications
3
40
0
Order By: Relevance
“…Moreover, IRF4 rearrangement may be observed in other LBCLs in association with BCL2 and/or MYC rearrangements, and these tumors should not be classified as LBCL-IRF4. 221 LBCL with 11q aberration (LBCL-11q) should be considered in tumors with high-grade/large-cell morphology, germinal center phenotype, and very high proliferation (>90%) without MYC rearrangement (Figure 4). Most LBCL-11q carry the prototypical 11q23.2-q23.3 gain/11q24-qter loss, but some have a single terminal loss or proximal gains together with terminal copy neutral loss of heterozygosity (CN-LOH).…”
Section: Pediatric B-cell Lymphomasmentioning
confidence: 99%
“…Moreover, IRF4 rearrangement may be observed in other LBCLs in association with BCL2 and/or MYC rearrangements, and these tumors should not be classified as LBCL-IRF4. 221 LBCL with 11q aberration (LBCL-11q) should be considered in tumors with high-grade/large-cell morphology, germinal center phenotype, and very high proliferation (>90%) without MYC rearrangement (Figure 4). Most LBCL-11q carry the prototypical 11q23.2-q23.3 gain/11q24-qter loss, but some have a single terminal loss or proximal gains together with terminal copy neutral loss of heterozygosity (CN-LOH).…”
Section: Pediatric B-cell Lymphomasmentioning
confidence: 99%
“…IRF4 was originally identified as the MUM1 gene from the chromosomal translocation t(6;14)(p25;q32) involving the IgH locus in MM cells [ 9 ]. Subsequent studies have demonstrated that IRF4 is highly expressed in various types of both B-lymphoid and T-lymphoid neoplasms, including multiple myeloma (MM) [ 9 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], diffuse large B-cell lymphoma (DLBCL) [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], Burkitt’s lymphoma (BL) [ 71 , 72 ], follicular lymphoma (FL) [ 61 , 73 , 74 ], anaplastic large-cell leukemia (ALCL) [ 75 , 76 , 77 , 78 , 79 , 80 , 81 ], adult T-cell leukemia/lymphoma (ATL) [ 10 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ], and mycosis fungoides (MF) [ 75 , 77 ]. Accordingly, various studies have demonstrated the functional requirement of IRF4 for cancer cell survival and proliferation.…”
Section: Oncogenic Mechanisms Mediated By Irf4mentioning
confidence: 99%
“…Given the oncogenic advantage conferred by IRF4 overexpression, a plethora of genetic mechanisms that aberrantly activate IRF4 exist, ranging from chromosomal translocations to genetic amplifications, mutations, and constitutive activation of upstream signaling pathways ( Figure 1 ). For instance, the IRF4 gene was found to be translocated with the IgH regulatory element in MM and DLBCL cases and with the TCRA locus in ALCL cases [ 9 , 54 , 63 , 64 , 76 ], which induces aberrant expression of IRF4 under a highly active transcriptional regulatory element. Another potential mechanism of IRF4 overexpression includes constitutive activation of NF-κΒ, which is an upstream factor of IRF4.…”
Section: Oncogenic Mechanisms Mediated By Irf4mentioning
confidence: 99%
“…MYC was considered as positive when greater than 40% of tumor cells exhibited staining. [12] A positive threshold was defined at 50% for BCL2 and MUM1, 30% for CD10 and BCL6. GCB phenotype was evaluated by antibodies of C10, BCL6, and MUM1.…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%
“…Previous work has shown the unfavorable prognosis determined by a concordant marrow infiltration, with lower progression-free survival and overall survival. [12] BM infiltration represents a subset with a poor prognosis, whereas the prognostic impact of discordant BM infiltration could be limited to ABC cases. [16] In our study, a disease involving multiple sites and bone marrow occurred in patients older than 40, predominantly presents with advanced stage and poor prognosis, indicating that these cases had molecular features similar to ABC cases and different from other DLBCL involving WR and GIT.…”
Section: Characteristics Of Different Involvements In Gcderived Dlbcl...mentioning
confidence: 99%